Analysis of the Influence of Entrepreneurial Competence and Entrepreneurial Orientation on MSME Performance: Literature Review Study - Ragil Cahyani; Hanim Rosita; Riska Puspita; Riyan Sisiawan Putra (CV. Proaksara Global Transeduka, 2024)
MSMEs play a crucial role in Indonesia's economy, contributing to the reduction of unemployment and supporting various aspects such as exports, investment, and the formation of Gross Domestic Product (GDP). This study seeks to examine the impact of entrepreneurial competence and entrepreneurial orientation on the performance of MSMEs. The research methodology involves a literature review and empirical studies from a range of previous research journals, utilizing the Garuda Ministry of Education and Culture database to select 4090 journals, with 15 chosen as references for this research. The findings indicate that entrepreneurial competence and entrepreneurial orientation both have a significant influence on MSME performance, highlighting the importance of these variables in shaping business performance in MSMEs. Future research could explore the addition of moderator or mediating variables relevant to the current era.